2003
DOI: 10.14358/pers.69.9.1011
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Physical Composition of Urban Morphology Using Multiple Endmember Spectral Mixture Models

Abstract: The application of multiple endmember spectral mixture analysis (MESMA) to map the physical composition of urban morphology using Landsat Thematic Mapper (TM) data is evaluated and tested. MESMA models mixed pixels as linear combinations of pure spectra, called endmembers, while allowing the types and number of endmembers to vary on a per-pixel basis. A total of 63 two-, three-, and four-endmember models were applied to a Landsat TM image for Los Angeles County, and a smaller subset of these models was chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(82 citation statements)
references
References 21 publications
0
70
0
4
Order By: Relevance
“…In fact, various definitions and methods exist for delineating urban boundaries of cities, including administrative boundaries [53], functional boundaries [54,55], and morphological boundaries [56,57]. In this paper, we defined the spatial extent of urban boundaries based on population density data.…”
Section: Application Of the Csi To Megacitiesmentioning
confidence: 99%
“…In fact, various definitions and methods exist for delineating urban boundaries of cities, including administrative boundaries [53], functional boundaries [54,55], and morphological boundaries [56,57]. In this paper, we defined the spatial extent of urban boundaries based on population density data.…”
Section: Application Of the Csi To Megacitiesmentioning
confidence: 99%
“…Several methods for retrieval of FVC using remote sensing have been developed including spectral mixture analysis (SMA) [2][3][4], artificial neural networks [5][6][7], fuzzy classifiers [8], maximum likelihood classifiers [9], regression trees [10][11][12], and simple regression based on the Normalized Difference Vegetation Index (NDVI) [13]. In particular, SMA has often been used to estimate FVC from multi-spectral remote sensing data [2,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Murray (2003), and Wu (2004) compared several spectral unmixing models for estimation of impervious surface distribution in Columbus, OH, and found that the three end-member V-I-S model (including brightness normalization) was the most effective. Other studies, however, have demonstrated the effectiveness of a variety of different end-member combinations, such as high-albedo, low-albedo, and vegetation (Small, 2002), the inclusion of shade as an end-member (Alberti et al, 2004;Lu & Weng, 2004), and allowance for variable numbers and types of end-members (Dennison & Roberts, 2003;Rashed et al, 2003). Lu and Weng (2004) demonstrated that green vegetation, shade, and soil or impervious surface were the most effective end-members for spectral unmixing in Indianapolis, IN.…”
Section: Introductionmentioning
confidence: 99%